PERBANDINGAN PENGARUH BAHAN BAKAR CPO OFF-GRADE DAN BIODIESEL B35 TERHADAP KEAUSAN PADA POMPA BAHAN BAKAR MESIN DIESEL - Buana, Erganata Surya (Universitas Muhammadiyah Metro, 2025)
As time progresses, the use of plant-based alternative fuels is increasing. However, these new alternative fuels can cause various issues in engines, one of which is increased wear on fuel pumps. This study aims to examine the wear rate of fuel pumps in diesel engines using off-grade CPO fuel and compare it to biodiesel B35. Experimental testing was conducted to obtain data on the wear rate of fuel pumps for both types of fuel under identical testing conditions. The parameters measured included the dimensions and mass of the fuel pump components, as well as the temperature of the coolant tank and intake pipe. The results of this study show that the fuel pump components in diesel engines using off-grade CPO experience higher wear rates compared to those using biodiesel B35. This is indicated by dimension measurements showing a difference of 0.24% and mass measurements showing a difference of 0.075%. The higher wear rate is attributed to the higher acid number and sulfur content in off-grade CPO. Additionally, the temperature of the coolant tank and intake pipe in engines using off-grade CPO was also higher compared to those using biodiesel B35, due to the higher oxygen content and the lower cetane number and flash point of off-grade CPO fuel.